The effect of motivation and work environment on the performance of Hotel Muria Semarang employees - Arta Adi Kusuma (Institute of Accounting Research and Novation (IARN), 2021)
The problems studied are how motivation, work environment and employee performance are, is there any influence of motivation and work environment on employee performance partially or simultaneously. This study aims to determine how the motivation, work environment and performance of Hotel Muria Semarang employees, to determine the effect of motivation and work environment on the performance of employees of Hotel Muria Semarang either partially or simultaneously. The population in this study were all 115 employees of Hotel Muria Semarang. The sample was determined by proportional random sampling technique, with 53 respondents. The data collection method used is a questionnaire method (questionnaire) and documentation. The data analysis method used in this study is the percentage description analysis method and multiple linear regression. Based on the research results obtained multiple linear regression equation Ŷ= 23.857 + 0.180 X1 + 0.94 X2. Using SPSS 16 the results of the F test hypothesis show F count = 16,646 with a significance value = 0.000 <0.05 which means H3 which reads